Ubiquitin-specific peptidase 10, a deubiquitinating enzyme: Assessing its role in tumor prognosis and immune response - Ye, Ziqi; Chen, Jie; Huang, Ping; Xuan, Zixue; Zheng, Shuilian (Frontiers in Oncology, 2022)
Ubiquitin-specific peptidase 10 (USP10) is a member of the ubiquitin-specific protease family that removes the ubiquitin chain from ubiquitin-conjugated protein substrates. We performed a literature search to evaluate the structure and biological activity of USP10, summarize its role in tumorigenesis and tumor progression, and discuss how USP10 may act as a tumor suppressor or a tumor-promoting gene depending on its mechanism of action. Subsequently, we elaborated further on these results through bioinformatics analysis. We demonstrated that abnormal expression of USP10 is related to tumorigenesis in various types of cancer, including liver, lung, ovarian, breast, prostate, and gastric cancers and acute myeloid leukemia. Meanwhile, in certain cancers, increased USP10 expression is associated with tumor suppression. USP10 was downregulated in kidney renal clear cell carcinoma (KIRC) and associated with reduced overall survival in patients with KIRC. In contrast, USP10 upregulation was associated with poor prognosis in head and neck squamous cell carcinoma (HNSC). In addition, we elucidated the novel role of USP10 in the regulation of tumor immunity in KIRC and HNSC through bioinformatics analysis. We identified several signaling pathways to be significantly associated with USP10 expression, such as ferroptosis, PI3K/AKT/mTOR, TGF-β, and G2/M checkpoint. In summary, this review outlines the role of USP10 in various forms of cancer, discusses the relevance of USP10 inhibitors in anti-tumor therapies, and highlights the potential function of USP10 in regulating the immune responses of tumors.